Reporting Non-GAAP Financial Measures - Isidro, H.; Marques, A.; Guillamon Saorin, E. (2020)
The voluntary disclosure of alternative performance measures (APMs) (also known as ‘non-GAAP’, ‘adjusted’, ‘pro-forma’ or ‘street’ earnings) to supplement financial results based on the generally accepted accounting principles is a widespread phenomenon, showing an increasing trend over time and an ever-higher discrepancy with their GAAP equivalents.